Genetic diversity of two viruses affecting lentil and chickpea crops in the highlands of Ethiopia - Kumari, Safaa; Moukahel, Abdulrahman; Ademe, Anteneh; Aynewa, Yetsedaw; Kemal, Seid Ahmed (International Center for Agricultural Research in the Dry Areas, 2022)
Chickpea and lentil are the major legume crops grown in Ethiopia, providing people with balanced nutrition of proteins, minerals, fibers, and carbohydrates. Since 2019, farmers in the highlands of Ethiopia are losing their crops because of virus epidemics, and lentil production area in Ethiopia was reduced due to the virus infection. Knowing genetic variation and the exact identity of viruses affecting crops is essential for breeding for resistance and crop management purposes. Serological tests for more than 2000 chickpea and lentil samples showed that the most important viruses are Chickpea chlorotic stunt virus (CpCSV) on both crops, and Pea seed-borne mosaic virus (PSbMV) on lentil. Representative samples were selected for further analysis with RT-PCR and sequence to identify the isolates at molecular level. Phylogenetic analysis showed that the Ethiopian PSbMV isolates (5 lentil & 1 chickpea) are clustered with pathotype 2, and CpCSV isolates (3 chickpea & 2 lentil) are clustered with Serogroup-I.